Weizmannia coagulans BC99 alleviates hyperuricemia and oxidative stress via DAF-16/SKN-1 activation in Caenorhabditis elegan - Gao, Yinyin; Li, Cheng; Li, Junfei; Duan, Mengyao; Li, Xuan; Zhao, Lina; Wu, Ying; Gu, Shaobin (Frontiers in Microbiology, 2024)
IntroductionHyperuricemia (HUA) refers to the presence of excess uric acid (UA) in the blood, which increases the risk of chronic kidney disease and gout. Probiotics have the potential to alleviate HUA.MethodsThis study established a hyperuricemia model using Caenorhabditis elegans (C. elegans), and studied the anti-hyperuricemia activity and potential mechanisms of Weizmannella coagulans BC99 (W. coagulans) at different concentrations (107 CFU/mL BC99, 108 CFU/mL BC99). Subsequently, we utilized UPLC-Q-TOF/MS to investigate the impact of BC99 on endogenous metabolites in C. elegans and identified pathways and biomarkers through differential metabolomics analysis.ResultsThe results of this study showed that BC99 treatment significantly reduced the expression of P151.2 and T22F3.3 (p < 0.05), reduced the levels of UA and xanthine oxidase (XOD) in nematodes (p < 0.05), while extending their lifespan and movement ability (p < 0.05). Mechanistically, BC99 activates the transcription factors DAF-16 and SKN-1, thereby inducing the expression of stress response genes, enhancing the activity of antioxidant enzymes and tolerance to heat stress in the body, and reducing the production of ROS (p < 0.001). This effect was most significant in the H-BC99 group. Furthermore, non-targeted metabolomics indicated that BC99 predominantly regulated pathways associated with amino acid metabolism (Carnosine), glycerophospholipid metabolism, and purine metabolism.DiscussionThese results underscore BC99 as an effective and economical adjunct therapeutic agent for hyperuricemia, providing a scientific basis for further development and application.